Correlation between High-Sensitive C-Reactive Protein and HighSensitive Troponin I with 6-Minute Walk Distance in Acute Myocardial Infarction - Putri Septiani; Heru Sulastomo; Niniek Purwaningtyas (ACI (Acta Cardiologia Indonesiana), 2019)
Background: Biomarker has a role in diagnosis and risk stratification of ischemic heart disease patients. Troponin has become the reference biomarker for acute myocardial infarction (AMI). However, some other biomarkers have benefit on prognostic value, such as C-Reactive Protein (CRP). Six-minute walk test (6MWT) could be performed to assess functional capacity in patients with heart disease.Aim: To assess the correlation between hsCRP and hsTroponin I with 6-minute walk distance (6MWD) in AMI patients.Method: This is an observational analytic study with prospective cohort design, conducted in August-September 2018. The subjects were AMI patients at Dr. Moewardi district general hospital, Surakarta. The hsCRP and hsTroponin I sampling was carried out on admission. 6MWT was performed before discharge. Statistical analysis was performed to assess the correlation. Then the ROC curve was used to determine the cut-off point, sensitivity and specificity.Result: 6MWD of 40 subjects was divided into 2 groups based on the mean distance (<378 m and ≥378 m). There was a significant negative correlation between hsCRP and 6MWD (r =-0.475, p =0.002), but no significant correlation between hsTroponin I and 6MWD (r =-0.048, p = 0.244). However, hsCRP together with hsTroponin I have a significant correlation with 6MWD (r =0.491, p =0.006). Using the ROC curve, obtained AUC of 0.725 and a cut-off point of 0.555 mg/l, as well as a sensitivity of 69.6% and specificity of 88.2%Conclusion: There was a significant negative relationship between hsCRP and 6MWD, but no significant relationship between hsTroponin I with 6MWD.HsCRP together with hsTroponin I have a significant correlation with 6MWD in AMI